The effect of systemic ibuprofen on gingival inflammation in humans - Taiyeb Ali, T.B.; Waite, I.M. (1993)
Abstract: This clinical trial investigated the influence of short-term ibuprofen therapy on the early phase of the treatment of adult chronic periodontitis. The subjects were 17 patients in good general health referred for specialist periodontal treatment, having moderate chronic adult periodontitis. A series of assessments were made every 2 weeks over an 8-week period, including evaluations of oral hygiene, gingival inflammation and probing pocket depths. All participants received oral hygiene instruction, and following baseline examinations, had half the dentition, chosen at random, treated by scaling and root planing. The patients were randomly distributed into 2 groups, a test group receiving a 14-day course of 800 mg ibuprofen daily, in 4 divided doses, and a control group who did not receive any drug regime. At the 2-week assessment following the drug regime, significantly greater reduction in gingival bleeding, colour and pocketing was detected in the test compared with the control group. The beneficial effects were less evident thereafter. Although clinical application of the regime used in this study would not be justified by these results, further research into anti-inflammatory agents as an adjunct in the treatment of periodontal diseases could be considered, in the light of the beneficial effect on gingivitis in the early phase of periodontal treatment reported.